2019
DOI: 10.1038/s41598-019-49195-w
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of lung microbiota discloses differences in adenocarcinoma and squamous cell carcinoma

Abstract: The lung is a complex ecosystem of host cells and microbes often disrupted in pathological conditions. Although bacteria have been hypothesized as agents of carcinogenesis, little is known about microbiota profile of the most prevalent cancer subtypes: adenocarcinoma (ADC) and squamous cell carcinoma (SCC). To characterize lung cancer (LC) microbiota a first a screening was performed through a pooled sequencing approach of 16S ribosomal RNA gene (V3-V6) using a total of 103 bronchoalveaolar lavage fluid sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 41 publications
(70 reference statements)
4
61
0
2
Order By: Relevance
“…Despite the fact that squamous cell lung cancer is often associated with adverse effects of external factors (for example, smoking) and possible colonization of the lung by bacteria contained in tobacco in such patients [34], bacterial communities of lung tumors of various histological types did not differ in their taxonomic diversity (alpha diversity and Shannon index), which has been found also in previous research [6,32]. Interestingly, in our study, adenocarcinomas were characterized by a higher percentage of Gram-positive bacteria than Gram-negative ones, which may reflect the relationship between the microbiome composition and the histological type of tumor.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Despite the fact that squamous cell lung cancer is often associated with adverse effects of external factors (for example, smoking) and possible colonization of the lung by bacteria contained in tobacco in such patients [34], bacterial communities of lung tumors of various histological types did not differ in their taxonomic diversity (alpha diversity and Shannon index), which has been found also in previous research [6,32]. Interestingly, in our study, adenocarcinomas were characterized by a higher percentage of Gram-positive bacteria than Gram-negative ones, which may reflect the relationship between the microbiome composition and the histological type of tumor.…”
Section: Discussionsupporting
confidence: 75%
“…Very few studies have investigated the association between the lung microbiome and clinicopathological features of lung cancer. It has been suggested that different patterns of the lung microbiome are associated with histological types and stages of lung cancer [6]. K. Leigh Greathouse et al have analyzed 143 lung cancer samples and found that genera Acidovorax, Klebsiella, Rhodoferax and Anaerococcus were enriched in lung squamous cell carcinomas compared to lung adenocarcinomas [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lung cancer microbiota is enriched in Proteobacteria and is more diverse in adenocarcinoma and squamous cell carcinoma, particularly in males and heavier smokers [91]. On the other hand, numerous miRNAs are differently expressed in lung disease [92,93], and miRNA-21 is overexpressed in lung cancer [94], and it is well known that numerous elements of the microbiota such as Bacteroides, Lactococcus lactis and Fusobacterium nucleatum are able to modify the expression of this miRNA [31,43,50].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been described in the literature to isolate bacterial DNA from BALF ( Supplementary Table 1 ; Charlson et al, 2011 ; Erb-Downward et al, 2011 ; Pragman et al, 2012 ; Willner et al, 2012 ; Borewicz et al, 2013 ; Han et al, 2014 ; Renwick et al, 2014 ; May et al, 2015 ; Bernasconi et al, 2016 ; Dickson et al, 2016a , b ; Laguna et al, 2016 ; Marsh et al, 2016 ; Wen et al, 2016 ; Frayman et al, 2017 ; Zemanick et al, 2017 ; Ahmed et al, 2018 ; Kloepfer et al, 2018 ; Pattaroni et al, 2018 ; Esther et al, 2019 ; Gomes et al, 2019 ; Jorth et al, 2019 ; Kyo et al, 2019 ; Schneeberger et al, 2019 ; Tong et al, 2019 ; Wang et al, 2019 ). In some instances, successful recovery of DNA has been associated with the utilization of large volumes of starting material.…”
Section: Resultsmentioning
confidence: 99%
“…Different DNA extraction techniques have been used to profile microbial communities from BALF samples; commercial silica column-based kits ( Charlson et al, 2011 ; Willner et al, 2012 ; Han et al, 2014 ; Renwick et al, 2014 ; May et al, 2015 ; Dickson et al, 2016b ; Laguna et al, 2016 ; Marsh et al, 2016 ; Wen et al, 2016 ; Zemanick et al, 2017 ; Ahmed et al, 2018 ; Pattaroni et al, 2018 ; Kyo et al, 2019 ; Schneeberger et al, 2019 ; Tong et al, 2019 ; Wang et al, 2019 ), magnetic beads-based procedures ( Erb-Downward et al, 2011 ; Pragman et al, 2012 ; Bernasconi et al, 2016 ; Frayman et al, 2017 ; Kloepfer et al, 2018 ; Esther et al, 2019 ; Gomes et al, 2019 ), homemade protocols ( Borewicz et al, 2013 ; Jorth et al, 2019 ), salt-extraction approaches or the use of cationic detergents in combination with the classical phenol-chloroform extraction technique ( Willner et al, 2012 ). However, not many studies have compared the efficiency of these protocols, particularly using samples from young children ( Willner et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%